Pengaruh Perputaran Total Aset, Modal Kerja, dan Solvabilitas Terhadap Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016 - Friska Darnawaty Sitorus; Hariati Tumangger; Sri Delvina Br Gurusinga; Lis Hotmaida (ARBITRASE: Journal of Economics and Accounting, 2020)
This research intends to understand whether partial or simultaneous Total Turnover, Working Capital, and Solvency has a significant effect on profitability in the manufacturing industry sector which is listed on the Indonesia Stock Exchange. The theory used is financial management and accounting, the method used is a quantitative approach, explanatory research character, by collecting documentation data, the type of data used is secondary data, sample data collection techniques using the purposive sampling system, data analysis used is linear regression multiple. The population used was 144 companies and a sample of 66 samples (198 samples in 4 years). The classic assumption test used is the normality test, the multicollinearity test, the autokoleration test and the heteroscedasticity test. The results of the coefficient of determination test show the total assets turnover, working capital, and solvency to profitability of 37.5%.